Specific evolution and gene family expansion of complement 3 and regulatory factor H in fish - Najafpour, Babak (2021)
The complement system comprises a large family of plasma proteins that play a central role in innate and adaptive immunity. To better understand the evolution of the complement system in vertebrates and the contribution of complement to fish immunity comprehensive in silico and expression analysis of the gene repertoire was made. Particular attention was given to C3 and the evolutionary related proteins C4 and C5 and to one of the main regulatory factors of C3b, factor H (Cfh). Phylogenetic and gene linkage analysis confirmed the standing hypothesis that the ancestral c3/c4/c5 gene duplicated early. The duplication of C3 (C3.1 and C3.2) and C4 (C4.1 and C4.2) was likely a consequence of the (1R and 2R) genome tetraploidization events at the origin of the vertebrates. In fish, gene number was not conserved and multiple c3 and cfh sequence related genes were encountered, and phylogenetic analysis of each gene generated two main clusters. Duplication of c3 and cfh genes occurred across the teleosts in a species-specific manner. In common, with other immune gene families the c3 gene expansion in fish emerged through a process of tandem gene duplication. Gilthead sea bream (Sparus aurata), had nine c3 gene transcripts highly expressed in liver although as reported in other fish, extra-hepatic expression also occurs. Differences in the sequence and protein domains of the nine deduced C3 proteins in the gilthead sea bream and the presence of specific cysteine and N-glycosylation residues within each isoform was indicative of functional diversity associated with structure. The diversity of C3 and other complement proteins as well as Cfh in teleosts suggests they may have an enhanced capacity to activate complement through direct interaction of C3 isoforms with pathogenic agents.